One Health in Action: Operational Aspects of an Integrated Surveillance System for Zoonoses in Western Kenya - Falzon, Laura C.; Alumasa, Lorren; Amanya, Fredrick; Kang'ethe, Erastus; Kariuki, Samuel; Momanyi, Kelvin; Muinde, Patrick; Murungi, Maurice K.; Njoroge, Samuel M.; Ogendo, Allan; Ogola, Joseph; Rushton, Jonathan; et al. (Frontiers in Veterinary Science, 2019)
Surveillance of diseases in Kenya is currently carried out by both human and animal health sectors. However, a recent evaluation highlighted the lack of integration between these sectors, leading to disease under-reporting and inefficiencies. This project aimed to develop an integrated and cost-effective surveillance and reporting system for fifteen zoonotic diseases piloted in the counties of Bungoma, Busia and Kakamega in western Kenya. Specifically, in this paper we describe the operational aspects of such a surveillance system. Interviews were carried out with key informants, and this was followed by field visits to identify sentinel sites and liaise with relevant stakeholders. Based on this information, a sampling strategy comprising 12 sentinel sites, 4 in each county, was developed. Each sentinel site comprised of a livestock market, 1-2 neighbouring slaughter houses/slabs, and a hospital in the vicinity; each of the 12 sites, was visited every 4 weeks for 20 cycles. At each site, animal or patient sampling included a clinical examination and collection of blood, faeces and nasal swabs; in slaughtered animals, mesenteric lymph nodes, hydatid cysts and flukes were also collected. At the end of each field visit, data on staff involved and challenges encountered were recorded, while biological samples were processed and tested for 15 zoonotic diseases in the field laboratory in Busia, Kenya. Public engagement sessions were held at each sentinel site to share preliminary results and provide feedback to both stakeholders and study participants. A livestock market visit lasted just over three hours, and the most common challenge was the frequent refusals of animal owners to participate in the study. At the slaughterhouses, visits lasted just under four hours, and challenges included poorly engaged meat inspectors or slaughter processes that were too quick for sampling. Finally, the hospital visits lasted around four hours, and the most frequent challenges included low patients turn-out, frequent staff turn-over leading to poor institutional memory, and difficulty in obtaining patient stool samples. Our experiences have highlighted the importance of engaging with local stakeholders in the field, while also providing timely feedback through public engagement sessions, to ensure on-going compliance.